PENYIMPANGAN BUDAYA DAN FUNGSINYA DALAM KUMPULAN CERPEN BUKAN PEREMPUAN KARYA SYARIF HIDAYATULLAH dkk. - Setia Naka Andrian (Sasindo : Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2014)
This research has done a study on the short stories collection Bukan Perempuanwhich includes a variety of living spaces that idealized like a values in religious,moslem, and Santri culture environments. On those short stories collection presented avariety of devices that make it strange as a medium to be used in a specific purpose,such as literary texts as cultural resistance.The problems are in what kinds were culture that deviates from cultural realityof pesantren and how far that deviation is meaningful for the stories on short storiescollection Bukan Perempuan. The approach used in this study is a sociological approachusing a hermeneutic study.The results that is conducted on five short stories on a short stories collectionhave described concern the culture that deviates from the cultural reality of pesantrenand how far those deviation is meaningful for the stories on short stories collectionBukan Perempuan which is more focused on cultural resistance through literary texts.The culture which deviates from the cultural reality of pesantren contained in some ofthese stories are ideology deviation, violations of norms in pesantren environtment.Keywords: Structure, Cultural Deviation